Analysis And Using of the Features Graphics Processors for Medical Problems (Texas Journal of Medical Science, 2022)
The main function of graphics processors since their inception has been graphics processing. Subsequently, after it became possible to program the processing of model vertices and pixels of rendered three-dimensional scenes using special programs, the architecture of graphic processors changed significantly. After the advent of the first general-purpose programmable graphics processors, it became possible to process commands not only for graphic data in vector form, but also to perform ordinary calculations for arbitrary data on a variety of special cores, while implementing data parallelism. Therefore, Graphics Processing Units show high efficiency rates when parallelizing programs that process a lot of data of the same type. Such programs include shaders: a vertex shader processes 3D vertices with different parameters, a pixel shader processes 2D pixels on the screen using interpolated data. Even before the advent of general-purpose kernels, there were attempts to simulate the processing of arbitrary data of the same type written into textures using pixel shaders, which, of course, gave a performance boost compared to the CPU. To develop an abstract model of the GPU, consider the general structure of modern GPUs, as well as models designed for their programming